2005
DOI: 10.5432/ijshs.3.286
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Power Output of the Upper Limbs During Overhead Throw with Stretch-Shortening Cycle

Abstract: The purpose of this study was to investigate the effect of the stretch-shortening cycle (SSC) on power output in overhead throwing and on the behavior of shoulder extensor muscles by means of kinematics, kinetics and EMG. Thirteen healthy men performed two kinds of medicine ball throw; concentric throw (CT) without SSC and rebound throw (RT) with SSC. All throws were videotaped using a high-speed camera. Kinematics and kinetics such as joint angle, joint torque and joint torque power of the upper limbs were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In contrast, during the SJ, the athlete descends into a semi-squat position and holds this position for approximately 3 seconds before takeoff. The performance of a movement with countermovement is almost always better than a movement without countermovement when there is no time-pressure present (5,7,44,58,67,74). For example, the height achieved or power produced during a CMJ is higher than during an SJ, and ball speed is greater during an overhead throw with countermovement than without countermovement.…”
mentioning
confidence: 99%
“…In contrast, during the SJ, the athlete descends into a semi-squat position and holds this position for approximately 3 seconds before takeoff. The performance of a movement with countermovement is almost always better than a movement without countermovement when there is no time-pressure present (5,7,44,58,67,74). For example, the height achieved or power produced during a CMJ is higher than during an SJ, and ball speed is greater during an overhead throw with countermovement than without countermovement.…”
mentioning
confidence: 99%
“…Moreover, with greater elbow flexion in the cocking phase, followed by an earlier extension, we could assume a more effective stretch-shortening cycle of spiking in upper arm muscles in the U-20 group, compared to the younger groups. 32 Greater elbow extension in a ball-hitting moment was found to be a factor that caused higher spike velocity, 6 but also had a risk of shoulder muscles injury. 33 Despite non-significant differences in the current study, we found that the youngest players performed less elbow extension in the ball-hitting moment.…”
Section: Discussion and Implicationmentioning
confidence: 98%